Swedish farmers - are they entrepreneurs? - Svensson, Johanna (2011)
The EU market is being deregulated, which sees Swedish farmers that have traditionally been governed by different support systems being forced to adapt to a free market system and having to deal with the concept of supply and demand. The farming sector has during the past several years experienced harder conditions and the deregulation of the market has directly affected farmers. The need for entrepreneurs and that way of thinking has been identified (McElwee, 2006). Swedish farmers are neither familiar with a free market or being required to think in an entrepreneurial manner, does this therefore implicate that Swedish farmers are not entrepreneurs?